TEKNIK RESPONSIVE WEB DESIGN BOOTSTRAP 4 SERTA PENERAPANNYA DALAM RANCANG BANGUN LAYOUT WEB - Santoso, Miftah Faroq (Jurnal Pilar Nusa Mandiri, 2019)
Technology development makes influences the way to access the internet, which generally uses Desktop and Notebook computers, giving to other alternatives, namely accessing the internet using Tablets and Smartphones. The problem is that the majority of web layout designs cannot adjust the layout size automatically for these devices, because the resolution size of each device is different. To overcome the existing problems, we need a responsive web design method and technique in order to produce web layouts that can adjust the size of screen resolution automatically. The method used by applying the concept of Responsive Web Design (RWD), so that web layouts can adapt to screen size. Responsive web design techniques can be done in several ways, including using manual techniques using CSS Media Query and implementing CSS Frameworks such as Bootstrap CSS. The test results showed that the implementation of responsive web layouts using Bootstrap was very effective and efficient because web designers only needed the main library from Bootstrap, which was then combined by modifying according to the wishes of the user.